The role of microbiota in the chronic prostatitis/chronic pelvis pain syndrome: a review - Deng, An-Qi; Yue, Shao-Yu; Niu, Di; Zhang, Dan-Dan; Hou, Bing-Bing; Zhang, Li; Liang, Chao-Zhao; Du, He-Xi (Frontiers in Microbiology, 2025)
Chronic prostatitis/Chronic pelvis pain syndrome (CP/CPPS), a kind of frequent urinary condition among adult males, has caused a lot of inconvenience to patients in life, whose pathogenesis is unclear. Current evidence suggests that it is most likely to be an autoimmune disease. Symbiotic microbes, a highly diverse biological community that harbors trillions of microbes in each region of the human body, have gradually made people realize their important role in immune regulation, material metabolism, and health maintenance. In recent years, increasing studies have shown a connection between microbiota and CP/CPPS. In view of this, we performed this review to summarize the literature pertaining to microbiota and its association with the pathophysiological mechanism of CP/CPPS. In addition, we gleaned the latest progress in the therapeutic strategy of CP/CPPS that related to microbiota regulation in order to offer new perspectives on the management of CP/CPPS.